Biomarcadores electrofisiológicos del sesgo atencional hacia la amenaza en excombatientes del conflicto armado colombiano - Gómez-Londoño, Diana; López-Hincapié, José David; Trujillo-Orrego, Natalia (Iatreia, 2019)
-